Gestión contable y nivel de cumplimiento tributario en la empresa pública de turismo y comunicación social La Maná (Emturcomlm), Cantón La Maná - Provincia De Cotopaxi, año 2022. - Escobar Cabrera, Lenin Omar (2023)
This research allows us to know the development of the accounting management and tax compliance of the company EMTURCOMLM, which has the general objective of evaluating the accounting management and its impact on tax compliance of the Public Company of Tourism and Social Communication La Maná (EMTURCOMLM) canton La Maná, period 2022, in the development of the research process, a mixed methodology was used, quantitative and qualitative. The qualitative method allowed the theoretical analysis from the perspective of several authors, and the quantitative allowed the statistical analysis of the same, supported by techniques such as the interview and the survey with their respective instruments, to achieve the success of the research, the study of the inherent risk of the company made using the COSO I questionnaire. In addition, a tax analysis of the company taking into consideration the 103 and 104 forms, finding simple findings in them that its inherent risk is low and that it has not been subjected to any variety of sanctions by the internal revenue service since it complies with satisfaction except for bit inconveniences or inconsistencies that it has had within the process within the manual established the needs of the accounting management for the operation and better performance of the company.